Euphemism as a Mechanism of the Internal Workings of the Politically Correct Language (Global Journal of Human-Social Science, 2019)
As a social phenomenon, the politically correct is very recent and operate in the perspective of defending the individual rights of marginalized segments. In this context, the object of this study refers to the politically correct language (PCL), which can be defined as the process of substitution of stigmatized variants for others that are considered positive or neutral. Thus, the purpose of this paper is to present the euphemism as an internal mechanism of functioning of the PCL, justified by the need to reflect on prestige variants in three semantic fields: disability, blackness and homosexuality. The corpus covers online collection of the newspaper Folha de S. Paulo, an important Brazilian journal. As a result, euphemism in PCL: i) softens pejorative meanings, ii) inscribe new meanings in variants in use, iii) is also associated with technical variants in areas such as health and law, and finally iv) can also be exaggerated, contributing to other negative meanings.
Keywords: euphemism; politically correct language; disability; blackness; homosexuality